Sperm competition: linking form to function - Humphries, Stuart (BioMed Central, 2008)
BACKGROUND: Using information from physics, biomechanics and evolutionary biology, we explore the implications of physical constraints on sperm performance, and review empirical evidence for links between sperm length and sperm competition (where two or more males compete to fertilise a female's eggs). A common theme in the literature on sperm competition is that selection for increased sperm performance in polyandrous species will favour the evolution of longer, and therefore faster swimming, sperm. This argument is based on the common assumption that sperm swimming velocity is directly related to sperm length, due to the increased thrust produced by longer flagella. RESULTS: We critically evaluate the evidence for links between sperm morphology and swimming speed, and draw on cross-disciplinary studies to show that the assumption that velocity is directly related to sperm length will rarely be satisfied in the microscopic world in which sperm operate. CONCLUSION: We show that increased sperm length is unlikely to be driven by selection for increased swimming speed, and that the relative lengths of a sperm's constituent parts, rather than their absolute lengths, are likely to be the target of selection. All else being equal, we suggest that a simple measure of the ratio of head to tail length should be used to assess the possible link between morphology and speed. However, this is most likely to be the case for external fertilizers in which females have relatively limited opportunity to influence a sperm's motility.